Tindak Tutur Asertif pada Iklan di Trans TV - Hastuti, Hastuti; Sudarmaji, Sudarmaji; Liana, Eva (LPPM STKIP PGRI Bandar Lampung, 2023)
Illocutionary speech acts are often used in everyday language as humans do when speaking. The focus of this research is the use of illocutionary speech acts in advertising language on television stations, analysis and interpretation of illocutionary speech acts and utterances in each illocutionary speech act, as well as food and drink advertisements on Trans Tv. This research approach is qualitative, and the type of speech act research is assertive. The data collection method for this research is by listening to and recording spoken conversations in written language research video advertisements for food and drinks. The research results found that there were 40 pieces of data including assertive type illocutionary speech acts.